Botulinum neurotoxin for sialorrhea: a first choice therapy - Karapantzou, Chrysa; Karapantzos, Ilias; Zarogoulidis, Paul; Karanikas, Michail; Thomaidis, Vasilis; Charalampidis, Charalampos (Annals of Research Hospitals, 2017)
This article emphasizes the therapeutic potential of botulinum neurotoxin (BoNT) in the autonomous nerve system disorder of sialorrhea, a pathologic situation found mainly in patients with neurologic deficits. Major applications that are well known to be treated with botulinum toxin in the head and neck area, include undesirable muscular dysfunctions and spasms, based on the toxins blocking effect on the neuromuscular junction transmitter acetylcholine. In the 90’s it became clear that BoNT could block the release of acetylcholine in gland tissues, too. A new era in the management of autonomic dysfunctions began. There have been numerous of treatments such as Frey’s syndrome, sialorrhea, facial and cranial hyperhidrosis reviewed. Ultrasound guided intraglandular injections of botulinum toxin type A into both the submandibular and parotid glands, have been noted to be effective at controlling sialorrhea in practice. The doses and injection techniques are described and further discussed in this article. The option of the minimal invasive, well tolerated BoNT injections into the major salivary glands is crucial for the best management of sialorrhea patients, avoiding the side-effects of anticholinergic medications. The indications of BoNT in the head and neck region are still expanding as physicians are finding out the therapeutic valuability of the toxin in otorhinolaryngology.